PERAN KEPEMIMPINAN DAN KOMUNIKASI DALAM PENYALURAN DANA DESA DI KABUPATEN MADIUN - Tohirin Tohirin (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to determine the role of leadership and communication as a success factor for the fastest distribution of Village Funds at the national level. Data were collected through interviews and focus group discussions with key informants from the Regent of Madiun, KPPN Madiun, DPMD Madiun, BPKAD Madiun, Directorate of General Transfer Funds, Directorate General of Fiscal Balance, Ministry of Finance. Information comes from the Regent level, Head of Office, Head of Division, Head of Section and staff. In addition, data were also obtained from other related documents. Data analysis was carried out qualitatively with processing stages in the form of transcription, reduction, categorization, and interpretation with reference to the research objectives. The results of the study indicate that in the distribution of Village Funds from the State General Treasury Account to the Village Treasury Account, there are 2 important factors that influence the speed of distribution of Village Funds, namely 1) Bureaucratic Leadership, 2) Interdepartmental Communication. The success of Madiun district can serve as an example for other regions to be able to follow their strategy related to the Village Fund with the aim of accelerating the business process of distributing Village Funds